Reorientation of Islamic Education Based on the Philosophy of Technology: Reinforcing the Role of Humanity and Spirituality Amid the Onslaught of Digitalization - Tubagus Panambaian; Ani Cahyadi (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
The rapid development of digital technology has given rise to a wave of disruption that penetrates all aspects of life, including Islamic education. This wave often brings negative impacts in the form of dehumanization and spiritual crises, where humans are positioned as objects of technology. This article aims to analyze the urgency of reorienting Islamic education based on the philosophy of technology as a fundamental effort to reaffirm the role of humans and spirituality amid the digital onslaught. This study uses a qualitative method with a literature study approach. Data were collected from various primary sources, such as classical Islamic philosophical texts and contemporary philosophy of technology literature, as well as secondary sources in the form of accredited national journals. Data analysis was conducted using descriptive-analytical and interpretative methods. The results of this study indicate that the philosophy of technology provides a critical analytical tool to view technology not merely as a neutral instrument, but rather as a structure that can shape human consciousness and values. Based on this view, the reorientation of Islamic education should be directed at three main aspects: 1) reconstruction of the education paradigm, from the adoption of technology to the wisdom of technology; 2) transformation of the curriculum that integrates digital literacy with the strengthening of spiritual values (monotheism and morality); and 3) revitalization of the role of educators as spiritual guides and digital companions. In conclusion, the reorientation of Islamic education based on the philosophy of technology becomes an inevitability to ensure that digital technology becomes a medium of humanization, not a tool of dehumanization